Konsep "Mahabbah" dalam Tasawuf Imam Al-Ghazali - Safitri, Aulia Wulan (Maliki Interdisciplinary Journal, 2024)
Sufism in Islam goes through various stages and situations. Although it involves several aspects, the undeniable core principle of Sufism is an Islamic-based morality drawn from the Qur'an with messages of patience, devotion, motivation, love and simplicity. Sufism aims for a direct relationship with God, portraying oneness with Him. Sufism and Sharia are considered inseparable, with scholars, including Imam al-Ghazali, attempting to harmonize the two. Imam al-Ghazali, an Islamic intellectual, influential in many fields, highlighted important concepts in his works, including tawhid, makhafah, mahabbah (love), and ma'rifat. The concept of mahabbah according to al-Ghazali, who stated that the most important love is love for Allah, and how this concept has influenced the deep understanding of religion and Sufism in Islam.